Sinkronisasi Norma Penegakan Hukum Pembalakan Hutan : Studi Komparatif Sanksi Kumulatif antara Undang-Undang Nomor 32 Tahun 2009 dan Undang-Undang Nomor 6 Tahun 2023 - Naufal Reza Ar Rafi; Deni Yusup Permana (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the synchronization of Illegal Logging law enforcement norms following the enactment of Law No. 6 of 2023 concerning Job Creation and to compare its cumulative sanctions with those of Law No. 32 of 2009 concerning Environmental Protection and Management. This study uses a normative juridical method with a statute approach. The results show that administrative violations are now prioritized for business actors in forest areas through the mechanism of Articles 110A and 110B of the Job Creation Law. Comparatively, Law No. 6 of 2023 applies the principle of lex posteriori derogat legi priori, which emphasizes economic benefits and certainty of the business climate through administrative sanctions, in contrast to the regime of Law No. 32 of 2009, which emphasizes the deterrent effect of cumulative criminal penalties.